Role of Glutathione in Neutrophil Chemotaxis in Periodontitis - Nurul Iman Binti Badlishah Sham; Melissa M. Grant (MDPI AG, 2023)
Periodontitis is a common non-communicable inflammatory disease that leads to the destruction of periodontal tissues and tooth loss. Initiated by the plaque biofilm, there is a strong innate immune response with an abundance of neutrophils in the periodontium of affected individuals. Previous reports have shown that the intracellular concentration of glutathione in peripheral blood neutrophils from periodontitis patients and the chemotactic ability of these cells are compromised. Furthermore, other studies have described that in oxidative stress conditions neutrophil chemotaxis is aberrant and causes the glutathionylation of F-actin, a key player in chemotaxis. In this study, the effects of glutathione-modulating compounds were assessed in neutrophils isolated from healthy donors, showing that the perturbation of glutathione homeostasis decreases the chemotaxis of neutrophils. Following this, the intracellular glutathione status and chemotactic ability of neutrophils isolated from periodontitis patients was compared to that of age- and sex-matched controls. A decrease in glutathione and chemotactic ability were confirmed. Finally, the proteome of these neutrophils was explored, demonstrating a change in the abundance of proteins involved in glutathione homeostasis. Together these data suggest that peripheral blood neutrophils from periodontitis patients are compromised in their ability to cope with oxidative stress and move.